BOOK REVIEW. HOW TO READ LITERATURE BY TERRY EAGLETON REVIEW-THE MACRO ASPECTS OF LITERARY CRITICISM - Ginanjar Gailea (Humaniora, 2015)
Terry Eagleton, the author of How to Read Literature, is a well-known British literary theorist, critic and public intellectual. He is a professor of English Literature at Lancaster University. Among his publications, Literary Theory: An Introduction (1983) is still the best one till nowadays. In How to Read Literature, Eagleton attempts to deal with the challenge of literary criticism at present. It is because students of literature often percept a literary work as what it says. The aspect of ‘literariness’ which is a work’s aesthetic form is not taken into account. A literary work, then, is a mere of writing that shares information to the readers as though a newspaper, text book or manual of computer does. Whereas, focusing on literary forms and directing our sensitivity to language (these are items mostly discussed in this book) can uncover a theoretical and political question of text (ix). What is meant by literary forms are all elements building a body of work such as “tone, mood, pace, genre, syntax, grammar, texture, rhythm, narrative structure, punctuation and ambiguity (2).”